ANALYSIS OF CATFISH CULTIVATION AND ECONOMIC ACTIVITIES ON THE INCOME OF FISH FARMING COMMUNITIES IN BANJARMASIN, SOUTH KALIMANTAN - Dodik Jatmika; Muhammad Nurdin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The aim of this research is to determine the effect of catfish cultivation and economic activities on domestic income of catfish in Banjarmasin, South Kalimantan. The population in this study were catfish farming breeders in Banjarmasin, South Kalimantan. The samples in this study were used as criteria based on the work of the community who cultivated catfish, totaling 67 random breeders cultivating catfish in Banjarmasin, South Kalimantan. Partially, catfish cultivation has an effect on the income of catfish farmers in Banjarmasin, South Kalimantan. Partially, economic activities influence the income of catfish farmers in Banjarmasin, South Kalimantan. Together, catfish cultivation and economic activities influence the income of catfish farmers in Banjarmasin, South Kalimantan. Catfish cultivation predominantly influences the income of catfish farmers compared to other economic activities in Banjarmasin, South Kalimantan.